Praktik Mediasi Rasulullah SAW (SULH) Dalam Penyelesaian Konflik Antar Kelompok - Tusriyanto, Tusriyanto; Basri, Basri (Ri'ayah: Jurnal Sosial dan Keagamaan, 2024)
The purpose of this research is to describe the mediation practices of the Prophet Muhammad SAW in resolving inter-group conflicts in Balinuraga, South Lampung. The presence of a diverse society is Indonesia's wealth that must be recognized, accepted, and respected, then realized in the motto "Bhinneka Tunggal Ika" (Unity in Diversity). This diversity has the potential to give rise to injustice, vertical conflicts between the center and regions as well as horizontal conflicts among various elements of society, ideological conflicts, religious conflicts, structural poverty, social disparities, and others. One of the conflicts that occurred was the inter-group conflict in Lampung which was a result of improper actions towards young women. As a result of the clash between the residents of Agom and Balinuraga, 14 people were killed, some were critically injured, and several houses were damaged. This research uses a qualitative method, as it prioritizes the quality of analysis rather than statistical data. The research conducted by the researcher is a case study research, which aims to study intensively about certain social units, including individuals, groups, institutions, and communities. Data collection techniques refer to the methods or steps used in this research, including observation, interviews, and documentation. Data analysis includes data reduction, data display, and conclusion drawing. Based on the research data, the resolution of inter-group conflicts in the village of Balinuraga is carried out through mediation activities as conducted by the Prophet Muhammad SAW by making a peace agreement documented through a written agreement, returning the community to the principle of religious harmony because fundamentally every religion teaches peace and rejects division, making differences as a divine decree that must be believed in its truth in line with the motto "Bhinneka Tunggal Ika" (Unity in Diversity) even though different but still one. If groups maintain peaceful agreements and manage cultural diversity, the situation becomes peaceful because no party feels aggrieved.